2012
DOI: 10.1371/journal.pone.0030111
|View full text |Cite
|
Sign up to set email alerts
|

Inter-Relationship between Testicular Dysgenesis and Leydig Cell Function in the Masculinization Programming Window in the Rat

Abstract: The testicular dysgenesis syndrome (TDS) hypothesis proposes that maldevelopment of the testis, irrespective of cause, leads to malfunction of the somatic (Leydig, Sertoli) cells and consequent downstream TDS disorders. Studies in rats exposed in utero to di(n-butyl) phthalate (DBP) have strongly supported the TDS concept, but so far no direct evidence has been produced that links dysgenesis per se to somatic cell dysfunction, in particular to androgen production/action during the ‘masculinization programming … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 36 publications
3
34
0
1
Order By: Relevance
“…This is supported by the fact that focal dysgenesis is inversely correlated with AGD in fetal life (this study and ref. 40) and adulthood (this study).…”
Section: Discussionsupporting
confidence: 48%
See 2 more Smart Citations
“…This is supported by the fact that focal dysgenesis is inversely correlated with AGD in fetal life (this study and ref. 40) and adulthood (this study).…”
Section: Discussionsupporting
confidence: 48%
“…Time-mated females were allocated randomly to receive vehicle control treatment or 750 mg/kg DBP (Sigma-Aldrich; 99% pure according to the supplier) in 1 ml/kg corn oil daily by oral gavage. The dose of DBP was chosen as it induces a high incidence of focal dysgenesis as well as profoundly suppressing testosterone production by fetal Leydig cells (40). Three DBP treatment groups were used in this study: DBP-FW (E13.5-E21.5), DBP-MPW (E15.5-E18.5), and DBP-LW (E19.5-E21.5).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…AGD was increased after postnatal fulvestrant treatment as compared to LPS‐treated group. Animal model studies have identified that AGD may provide the means for retrospectively determining foetal androgen exposure during masculinisation and male reproductive tract development (van den Driesche, Kolovos, Platts, Drake, & Sharpe, ; Welsh, ). AGD decreased in male mice at PND26 after maternal LPS treatment from E13 to E17 (Wang et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Certain similarities in humans of these malformations in rodents, described as testicular dysgenesis syndrome (TDS), are speculated to be caused by exposure to anti-androgenic chemicals, which could result from reduced androgen action during fetal development (Skakkebaek et al, 2001;Wohlfahrt-Veje et al, 2009). For example, it has been shown that exposure of rats in utero to DBP can induce a TDS-like syndrome in the male offspring (Mylchreest et al, 2000;Fisher et al, 2003;Foster, 2006;Dean et al, 2012;van den Driesche et al, 2012), which is manifested as dose-dependent induction of cryptorchidism, hypospadias, and impaired spermatogenesis/infertility ( Fig. For example, it has been shown that exposure of rats in utero to DBP can induce a TDS-like syndrome in the male offspring (Mylchreest et al, 2000;Fisher et al, 2003;Foster, 2006;Dean et al, 2012;van den Driesche et al, 2012), which is manifested as dose-dependent induction of cryptorchidism, hypospadias, and impaired spermatogenesis/infertility ( Fig.…”
Section: Introductionmentioning
confidence: 99%